Differences Between Blood Pressure Between Before And After Giving Black Cincau (Mesona palustris BI.) In Trimester Ii Pregnant Women Who Have Hypertension - Maduratna, Enggal Sari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Hypertension or high blood pressure disease occurs due to the presence of blood vessels that tighten to make blood pressure increases that can be handled by using traditional treatment of black jaws. Based on preliminary study results obtained 80 pregnant women who experience hypertension. The objectives of the study analyzed the difference of black jaws to high blood pressure in second trimester pregnant women at BPM Nurul Muhimmah, S.SiT Kedung Kendo Village, Candi District of Kamal Regency.